Novice Teacher Supports the Mathematics Learning of English Language Learners in Any Language - Miller, Meghan; Zhang, Aidong "Linda"; DeLoach Johnson, Iris; Yang, Jianan "Gianna" (Ohio Journal of School Mathematics, 2023)
A novice teacher reflects on her first class of ELLs who spoke many native languages and shares her journey to improve. Three bang-for-the-buck strategies are shared. Support for her actions is provided through connections to the literature. Readers are encouraged to bravely move forward to use trial-and-error as they attempt to implement what they are learning from the many available resources which include anchor charts, sentence frames, manipulatives, and technology.